A comparative study of baseball bat performance - Nathan, A. M.; Crisco, J. J.; Greenwald, R. M.; Russell, D. A.; Smith, L. V. (Sports Engineering, 2011)
The results of a comparative study of five aluminum and one wood baseball bats are presented. The study includes an analysis of field data, high-speed laboratory testing, and modal analysis. It is found that field performance is strongly correlated with the ball-bat coefficient of restitution (BBCOR) and only weakly correlated with other parameters of the bat, suggesting that the BBCOR is the primary feature of a bat that determines its field performance. It is further found that the instantaneous rotation axis of the bat at the moment of impact is very close to the knob of the bat and that the rotational velocity varies inversely with the moment of inertia of the bat about the knob. A swing speed formula is derived from the field data and the limits of its validity are discussed. The field and laboratory measurements of the collision efficiency are generally in good agreement, as expected on theoretical grounds. Finally, the BBCOR is strongly correlated with the frequency of the lowest hoop mode of the hollow bats, as predicted by models of the trampoline effect.